Interplay of Plasma Membrane and Vacuolar Ion Channels, Together with BAK1, Elicits Rapid Cytosolic Calcium Elevations in Arabidopsis during Aphid Feeding. Issue 6 (30th May 2017) - Vincent, Thomas R.; Avramova, Marieta; Canham, James; Higgins, Peter; Bilkey, Natasha; Mugford, Sam T.; Pitino, Marco; Toyota, Masatsugu; Gilroy, Simon; Miller, Anthony J.; Hogenhout, Saskia A.; Sanders, Dale
Abstract : During feeding by aphids in vivo, a fluorescent calcium sensor reveals a mesophyll calcium signal that is dependent on BAK1, GLR3.3/GLR3.6, and TPC1. Abstract: A transient rise in cytosolic calcium ion concentration is one of the main signals used by plants in perception of their environment. The role of calcium in the detection of abiotic stress is well documented; however, its role during biotic interactions remains unclear. Here, we use a fluorescent calcium biosensor (GCaMP3) in combination with the green peach aphid ( Myzus persicae ) as a tool to study Arabidopsis thaliana calcium dynamics in vivo and in real time during a live biotic interaction. We demonstrate rapid and highly localized plant calcium elevations around the feeding sites of M. persicae, and by monitoring aphid feeding behavior electrophysiologically, we demonstrate that these elevations correlate with aphid probing of epidermal and mesophyll cells. Furthermore, we dissect the molecular mechanisms involved, showing that interplay between the plant defense coreceptor BRASSINOSTEROID INSENSITIVE-ASSOCIATED KINASE1 (BAK1), the plasma membrane ion channels GLUTAMATE RECEPTOR-LIKE 3.3 and 3.6 (GLR3.3 and GLR3.6), and the vacuolar ion channel TWO-PORE CHANNEL1 (TPC1) mediate these calcium elevations. Consequently, we identify a link between plant perception of biotic threats by BAK1, cellular calcium entry mediated by GLRs, and intracellular calcium release by TPC1 during a biologically relevant interaction.